Multiple effects of the Na+/H+ antiporter inhibitor HMA on cancer cells - Guaman Ortiz, L. (2017)
Amiloride derivatives are a class of new promising chemotherapeutic agents. A representative member of this family is the sodium-hydrogen antiporter inhibitor HMA (5-(N,N-hexamethylene amiloride), which has been demonstrated to induce cellular intracytosolic acidification and cell death through the apoptotic pathway(s). This work aims at characterizing drug response of human cancer cell lines to HMA. After a first screening revealing that HMA interferes with cancer cell survival, we focused our attention on SW613-B3 colon carcinoma cells, which are intrinsically resistant to a panel of drugs. Searching for the activation of canonical apoptosis, we found that this process was abortive, given that the final steps of this process, i.e. PARP-1 cleavage and DNA ladder, were not detectable. Thus, we addressed caspase-independent paradigms of cell death and we observed that HMA promotes the induction of the LEI/L-DNase II pathway as well as of parthanatos. Finally, we explored the possible impact of autophagy of cell response to HMA, providing the evidence that autophagy is activated in our experimental system. On the whole, our results defined the biochemical reactions triggered by HMA, and elucidated its multiple effects, thus adding further complexity to the intricate network leading to drug resistance.